A study on the furniture requirements and bedroom layout fitted for adolescent males - De Jesus, Louella C.; Mayo, Adelaida Villaraza (1995.)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (BID)--University of the Philippines Diliman.
Keywords: Bedroom furniture -- Philippines; Bedrooms -- Designs and plans